No evidence of cardiomyopathy in spinal and bulbar muscular atrophy. (16th May 2013) - Querin, G.; Melacini, P.; D'Ascenzo, C.; Morandi, L.; Mazzini, L.; Silani, V.; Romito, S.; Mandrioli, J.; Raimondi, M.; Pegoraro, E.; Soraru', G.
Abstract : Objectives: Spinal and bulbar muscular atrophy (SBMA) is a lower motor neuron disease caused by a CAG repeat expansion within the androgen receptor (AR) gene. Toxic nuclear accumulation of mutant AR has been observed in tissues other than nervous system including cardiac muscle. Moreover, CAG polymorphism length within AR has been associated with an increased risk of heart disease. Materials and methods: To test the hypothesis of the presence of cardiomyopathy in SBMA, a full cardiac protocol was applied to 25 SBMA patients. Results: Patients' age ranged between 32 and 75 years. Cardiologic examination, 12‐lead ECG, and echocardiography showed no abnormalities other than those consistent with hypertensive heart disease. One patient showed frequent supraventricular premature beats in absence of other significant arrhythmias at the 24‐h ECG Holter. Conclusions: Our findings do not support the hypothesis of a primary cardiomyopathy in SBMA.